A review of the maximal oxygen uptake values necessary for different running performance levels - Legaz Arrese, A.; Munguia Izquierdo, D.; Moliner Urdiales, D. (New Studies in Athletics, 2005)
It has been postulated that VO2max is not a good predictor of running performance in homogeneous groups of runners and a plateauing of the VO2max values has been documented in elite athletes. Nevertheless, elite endurance runners exhibit high VO2max values, suggesting this helps them gain membership in the top performance cluster. Knowing the VO2max values of groups of athletes is considered important for determining the maximum limit of performance of an athlete and am important aspect in the process of talent identification. One hundred and ninety top-class runners (137 males and 53 females) volunteered to participate in the study in which VO2max was calculated by means of a progressive test in treadmill. Runners were classified into groups in accordance with their best performance capabilitie. Up to 1500m, an increment in VO2max was observed and related to duration of the event. The VO2max for elite athletes in the 3000m, 5000m, 10,000 m and marathon groups did not differ significantly. Bibliographic analysis revealed small differences in VO2max among groups with similar performance levels and significant differences among groups that differ from important form in the performance.